2011
DOI: 10.1007/s11147-011-9066-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of hedge funds as primary lenders

Abstract: Hedge funds, Bank borrowers, Bond issuers, Lending, D82, G14, G23,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Hedge funds have become comparable with mutual funds in terms of asset management capabilities, and are an important new type of institutional investors (Chen et al ., ). Previous literature on hedge funds in advanced countries has shown that they are distinct from mutual funds in several ways: compared with market benchmarks, mutual fund managers do not have superior market timing or stock selection abilities (Goetzmann et al ., ), while hedge fund managers generally have superior investment experience and professional ability (Stulz, ; Agarwal and Meneghetti, ). Despite the dramatic development of hedge funds in China, there have been very few studies on this subject.…”
Section: Introductionmentioning
confidence: 99%
“…Hedge funds have become comparable with mutual funds in terms of asset management capabilities, and are an important new type of institutional investors (Chen et al ., ). Previous literature on hedge funds in advanced countries has shown that they are distinct from mutual funds in several ways: compared with market benchmarks, mutual fund managers do not have superior market timing or stock selection abilities (Goetzmann et al ., ), while hedge fund managers generally have superior investment experience and professional ability (Stulz, ; Agarwal and Meneghetti, ). Despite the dramatic development of hedge funds in China, there have been very few studies on this subject.…”
Section: Introductionmentioning
confidence: 99%